2016
DOI: 10.1093/ijnp/pyv132
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-Methyltransferase Val158Met Polymorphism and Clinical Response to Antipsychotic Treatment in Schizophrenia and Schizo-Affective Disorder Patients: a Meta-Analysis

Abstract: Background:The catechol-O-methyltransferase (COMT) enzyme plays a crucial role in dopamine degradation, and the COMT Val158Met polymorphism (rs4680) is associated with significant differences in enzymatic activity and consequently dopamine concentrations in the prefrontal cortex. Multiple studies have analyzed the COMT Val158Met variant in relation to antipsychotic response. Here, we conducted a meta-analysis examining the relationship between COMT Val158Met and antipsychotic response.Methods:Searches using Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 65 publications
4
44
0
Order By: Relevance
“…In a 10-study meta-analysis from 2016, met/met patients were much more likely to respond to antipsychotic treatment (greater reduction in positive symptoms) and showed a greater decrease in negative symptoms with increased cognitive function. Another interesting finding from this study was a post hoc analysis demonstrating this response in patients treated with atypical antipsychotics but no difference in patients treated with typical antipsychotics 20. However, 1 study included in the meta-analysis featured patients with the val/val genotype, who were more likely to respond to clozapine and have a reduction in their symptoms 21.…”
Section: Resultsmentioning
confidence: 71%
“…In a 10-study meta-analysis from 2016, met/met patients were much more likely to respond to antipsychotic treatment (greater reduction in positive symptoms) and showed a greater decrease in negative symptoms with increased cognitive function. Another interesting finding from this study was a post hoc analysis demonstrating this response in patients treated with atypical antipsychotics but no difference in patients treated with typical antipsychotics 20. However, 1 study included in the meta-analysis featured patients with the val/val genotype, who were more likely to respond to clozapine and have a reduction in their symptoms 21.…”
Section: Resultsmentioning
confidence: 71%
“…3 The most recent meta-analysis indicated that COMT was associated with psychological symptoms and cognitive characteristics as well as antipsychotic response in schizophrenia patients. 4 In addition, COMT has also been found to be associated with positive symptoms, 5,6 negative symptoms, 7,8 manic symptoms, 9 and cognitive deficits in schizophrenia. [10][11][12] In terms of epigenetic studies, investigations into the association between COMT DNA methylation and schizophrenia have focused on two isoforms: the soluble isoform (S-COMT) and the membranebound isoform (MB-COMT).…”
Section: Aimmentioning
confidence: 99%
“…Accumulating evidence has suggested the involvement of COMT genotypes in the pathophysiology of schizophrenia . The most recent meta‐analysis indicated that COMT was associated with psychological symptoms and cognitive characteristics as well as antipsychotic response in schizophrenia patients . In addition, COMT has also been found to be associated with positive symptoms, negative symptoms, manic symptoms, and cognitive deficits in schizophrenia …”
mentioning
confidence: 99%
“…These previous findings converge to indicate that the reciprocal interactions between COMT genotype, dopamine levels, and structural and/or functional alterations in the human brain are related to mental disorder symptoms, such as AVHs (Lu et al., 2007; Kang et al., 2010; Sagud et al., 2010; Gothelf et al., 2011; Edgar et al., 2012; Tian et al., 2013a,b; Li et al., 2015; Huang et al., 2016; Steiner et al., 2018). …”
Section: Introductionmentioning
confidence: 99%